The Role of Police in Terrorism Prevention: Indonesia’s Police Against ISIS Threat Case Study - Slamet Urip Widodo (Budapest International Research and Critics University, 2022)
The police have a central role in prevention, law enforcement, and deradicalization of terrorism in Indonesia. In view of counterterrorism itself, the ultimate mission and the most ideal condition to achieve is to prevent acts of terrorism that could have occurred. With regard to these preventive duties, the police have the ability to understand conditions in the community more effectively. This stems from the basic nature of the police which is the guardian and servant of the community, therefore the understanding of the source of problems in the community can be more effective. This becomes a natural advantage of the police compared with the military, which makes the police very dominant in terms of prevention of terrorism. Based on understanding of the role of the police in terms of prevention, it is necessary to have an understanding of social complexity which is the root of terrorism problems. Human security is a form of contemporary security arose from the demands to the state to protect the community further. In contrast to the war situation, after the cold war, this approach grew among others, by globalizing demilitarization and strengthening the police as a civil defense institution. Reflecting to Indonesia, it is understood that the police has the affairs of overcoming threats on humans, in contrast to the military affair in combating threats to the territory. Police have the ability to be close to the root of the problems of today's society, including horizontal and vertical conflict.Abrahms, Max. (2010). What Terrorists Really Want? Terrorist Motives and Counterterrorism Strategy. Stanford University.Asyraini, Siti, Fristy, Poppy, Octiva, Cut Susan, Nasution, M. Hafiz Akbar, & Nursidin, M. (2022). Peningkatan Kesadaran Protokol Kesehatan di Masa Pandemi Bagi Warga di Desa Selamat Kecamatan Biru-biru. Jurnal Pengabdian Kontribusi (Japsi), 2(1), 33-36.Crenshaw, M. (1985). An Organizational Approach to the Analysis of Political Terrorism. Orbis, 29, 465-489.Golose, Petrus Reinhard. (2009). Deradikalisasi Terorisme, Humanis, Soul Approach dan Menyentuh Akar Rumput. Jakarta: YPTIK.Jibril, Ahmad, Cakranegara, Pandu Adi, Putri, Raudya Setya Wismoko, & Octiva, Cut Susan. (2022). Analisis Efisiensi Kerja Kompresor pada Mesin Refrigerasi di PT. XYZ. Jurnal Mesin Nusantara, 5(1), 86-95.Octiva, Cut Susan. (2018). Pengaruh Pengadukan pada Campuran Limbah Cair Pabrik Kelapa Sawit dan Tandan Kosong Kelapa Sawit terhadap Produksi Biogas. Tesis. Medan: Fakultas Teknik, Program Studi Teknik Kimia, Universitas Sumatera Utara. https://repositori.usu.ac.id/bitstream/handle/123456789/12180/157022002.pdf?sequence=1&isAllowed=y.Octiva, C. S., Irvan, Sarah, M., Trisakti, B., & Daimon, H. (2018). Production of Biogas from Co-digestion of Empty Fruit Bunches (EFB) with Palm Oil Mill Effluent (POME): Effect of Mixing Ratio. Rasayan J. Chem., 11(2), 791-797.Octiva, Cut Susan, Indriyani, & Santoso, Ari Beni. (2021). Effect of Stirring Co-digestion of Palm Oil and Fruith for Biogas Production to Increase Economy Benefit. Budapest International Research and Critics Institute-Journal, 4(4), 14152-14160. DOI: https://doi.org/10.33258/birci.v4i4.3521.Pandia, S., Tanata, S., Rachel, M., Octiva, C., & Sialagan, N. (2018). Effect of Fermentation Time of Mixture of Solid and Liquid Wastes from Tapioca Industry to Percentage Reduction of TSS (Total Suspended Solids). IOP Conference Series: Materials Science and Engineering, 309, 012086. DOI: 10.1088/1757-899X/309/1/012086.Pandiangan, Saut Maruli Tua. (2015). Analisis Lama Mencari Kerja Bagi Tenaga Kerja Terdidik di Kota Medan. Skripsi. Medan: Fakultas Ekonomi dan Bisnis, Program Studi Ekonomi Pembangunan, Universitas Sumatera Utara. https://www.academia.edu/52494724/Analisis_Lama_Mencari_Kerja_Bagi_Tenaga_Kerja_Terdidik_di_Kota_Medan. Pandiangan, Saut Maruli Tua. (2018). Analisis Faktor-faktor yang Mempengaruhi Penawaran Tenaga Kerja Lanjut Usia di Kota Medan. Tesis. Medan: Fakultas Ekonomi dan Bisnis, Program Studi Ilmu Ekonomi, Universitas Sumatera Utara. http://repositori.usu.ac.id/bitstream/handle/123456789/10033/167018013.pdf?sequence=1&isAllowed=y.Pandiangan, Saut Maruli Tua, Rujiman, Rahmanta, Tanjung, Indra I., Darus, Muhammad Dhio, & Ismawan, Agus. (2018). An Analysis on the Factors which Influence Offering the Elderly as Workers in Medan. IOSR Journal of Humanities and Social Science (IOSR-JHSS), 23(10), 76-79. DOI: 10.9790/0837-2310087679. http://www.iosrjournals.org/iosr-jhss/papers/Vol.%2023%20Issue10/Version-8/K2310087679.pdf.Pandiangan, Saut Maruli Tua, Resmawa, Ira Ningrum, Simanjuntak, Owen De Pinto, Sitompul, Pretty Naomi, & Jefri, Riny. (2021). Effect of E-Satisfaction on Repurchase Intention in Shopee User Students. Budapest International Research and Critics Institute-Journal, 4(4), 7785-7791. DOI: https://doi.org/10.33258/birci.v4i4.2697.Pandiangan, Saut Maruli Tua, Oktafiani, Fida, Panjaitan, Santi Rohdearni, Shifa, Mutiara, & Jefri, Riny. (2022). Analysis of Public Ownership and Management Ownership on the Implementation of the Triple Bottom Line in the Plantation Sector Listed on the Indonesia Stock Exchange. Budapest International Research and Critics Institute-Journal, 5(1), 3489-3497. DOI: https://doi.org/10.33258/birci.v5i1.4016.Pandiangan, Saut Maruli Tua. (2022). Effect of Packaging Design on Repurchase Intention to the Politeknik IT&B Medan Using E-Commerce Applications. Journal of Production, Operations Management and Economics (JPOME), 2(1), 15–21. http://journal.hmjournals.com/index.php/JPOME/article/view/442.Tobing, Murniati, Afifuddin, Sya’ad, Rahmanta, Huber, Sandra Rouli, Pandiangan, Saut Maruli Tua, & Muda, Iskandar. (2018). An Analysis on the Factors Which Influence the Earnings of Micro and Small Business: Case at Blacksmith Metal Industry. Academic Journal of Economic Studies, 5(1), 17-23. https://www.ceeol.com/search/article-detail?id=754945.Yunanto, Dr. Sri. (2017). Ancaman dan Strategi Penanggulangan Terorisme di Dunia dan Indonesia. Institute for Peace and Security Studies.